Teacher agency, linguistic diversity, and everyday multiculturalism appropriating MTB-MLE policy in Bongao, Tawi-Tawi - Colicol, Fernigil L.
Informed by anthropology and sociology of education, this ethnographic study aimed to foreground teacher agency in the language-in-education policy by exploring how it was achieved in the Mother Tongue Based-Multilingual Education (MTB-MLE) implementation by the teachers at the Mindanao State University Integrated Laboratory School (MSU-ILS) in Bongao, Tawi-Tawi, a linguistically diverse and conflict-affected province in the Bangsamoro, Philippines. Specifically, it focused on (a) the contextual factors in language use, (b) the teacher agency, and (c) the consequences of teacher agency in the MTB MLE implementation.